2015
DOI: 10.1016/j.snb.2014.11.077
|View full text |Cite
|
Sign up to set email alerts
|

Technological development of intracellular polysilicon–chromium–gold chips for orthogonal chemical functionalization

Abstract: Increasingly, advances in microtechnologies are focused on obtaining new chips intended for applications in fields such as nanomedicine and cell biology, taking advantage of the ability of microelectronics to manufacture devices with cell dimensions and a large variety of features. Here, we report a technology for the fabrication of multi-material chips, using polysilicon and gold as device layers, to be used as bi-functional cellinternalizable devices. In our case, one of the main technological challenges is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The microparticles (mP) used in this study were prepared as described elsewhere; 48 and consist of a layer of polysilicon and a layer of gold attached by a thin chromium layer. Three different samples were prepared: a control sample containing MTMS and MHEG (PEG-mP), a sample with MTMS and ATPP-LA (ATPP-LA-mP), and a sample with MTMS and ZnATPP-LA (ZnATPP-LA-mP).…”
Section: Functionalization Of Microparticles (Mp)mentioning
confidence: 99%
See 3 more Smart Citations
“…The microparticles (mP) used in this study were prepared as described elsewhere; 48 and consist of a layer of polysilicon and a layer of gold attached by a thin chromium layer. Three different samples were prepared: a control sample containing MTMS and MHEG (PEG-mP), a sample with MTMS and ATPP-LA (ATPP-LA-mP), and a sample with MTMS and ZnATPP-LA (ZnATPP-LA-mP).…”
Section: Functionalization Of Microparticles (Mp)mentioning
confidence: 99%
“…S18 † for microfabrication details). 48 Fig. 2 shows the SEM images of the NR and the microparticles, prior to functionalization, depicting their shape, dimensions and surface composition.…”
Section: Synthesis and Characterization Of Porphyrin-functionalized Gmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that a residue of EDTA is retained on the gold surface even after thiol‐OEG deposition. Binding of APTES to gold has previously been reported,[22b,26] and it might be that this also entails the retention of EDTA. We found that the surfaces exposed to orthogonal functionalization also showed good retention of their activity during repeated use over the course of at least 1 month (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%